(3egPH GdSff GdocHQi ddHjgbjs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3CHh HcQ eMeO GdHjgbjs
(3BNQgG (B:s
(3BNQ HGH Gdfgj Yf GdUdGI YfO WdhY GdTeS hYfO ZQhHgG s
(3GdfSNI HgG MhGTs
(3fbdkG Yf NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
Keywords: (3GdMOjK h GdeUWdMs